2019
DOI: 10.1038/s41598-019-51781-x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-aminobutyric acid-producing lactobacilli positively affect metabolism and depressive-like behaviour in a mouse model of metabolic syndrome

Abstract: Metabolic and neuroactive metabolite production represents one of the mechanisms through which the gut microbiota can impact health. One such metabolite, gamma-aminobutyric acid (GABA), can modulate glucose homeostasis and alter behavioural patterns in the host. We previously demonstrated that oral administration of GABA-producing Lactobacillus brevis DPC6108 has the potential to increase levels of circulating insulin in healthy rats. Therefore, the objective of this study was to assess the efficacy of endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 70 publications
2
74
1
Order By: Relevance
“…These findings suggest that fecal GABA level in the patients with MDD may be modulated by a panel of gut microbes, which may be implicated in the development of MDD. In line with our assumption, a previous study has shown that microbial-derived GABA may influence the host through the gut-brain axis (29), and GABA-producing microbes can improve depression-like behavior (30). Thus, we boldly speculate that the decrease in gut GABA level may be correlated with the dysregulation of GABAergic function in the brain (31).…”
Section: Discussionsupporting
confidence: 87%
“…These findings suggest that fecal GABA level in the patients with MDD may be modulated by a panel of gut microbes, which may be implicated in the development of MDD. In line with our assumption, a previous study has shown that microbial-derived GABA may influence the host through the gut-brain axis (29), and GABA-producing microbes can improve depression-like behavior (30). Thus, we boldly speculate that the decrease in gut GABA level may be correlated with the dysregulation of GABAergic function in the brain (31).…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that mental disorders, such as depression, are negatively correlated with the abundance of GABA-producing Bacteroides [ 14 ]. Further, accumulating evidence from animal trials suggests that the ingestion of GABA-producing bacteria supports relief from psychiatric illnesses, such as depression, and physical ailments, such as diabetes [ 15 , 16 , 17 ]. As the majority of available evidence for GABA’s relation to microbial composition has been performed in animals, there is a need for more evidence from human cohorts to encourage the application of these microbes as probiotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma-amino butyric acid (GABA), is a small organic molecule composed of amino and carboxylic functional groups. It is a non-protein amino acid that is distributed broadly in biological systems [ 26 ] and a major inhibitory neurotransmitter in the human central nervous system [ 27 , 28 ]. Due to the non-toxicity of GABA, its simplicity, and its bi-functionality, we utilize it here as a modifying surface agent in the synthesis of ZnO NPs for controlling the size and morphology of the ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%